2018
DOI: 10.2174/1570159x15666170602112851
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death after Intracerebral Hemorrhage

Abstract: Background: Intracerebral hemorrhage (ICH) accounts for up to 15% of all strokes and is characterized by high rates of mortality and morbidity. The post-ICH brain injury can be distinguished in 1) primary, which are caused by disrup-tion and mechanical deformation of brain tissue due to hematoma growth and 2) secondary, which are induced by microglia activation, mitochondrial dysfunction, neurotransmitter and inflammatory mediator release. Although these events typically lead to necrosis, the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 145 publications
1
57
0
5
Order By: Relevance
“…Previous studies have shown that activation of apoptosis plays an important role in the pathology of brain injury triggered by ICH [39,40]. The results of TUNEL staining (Fig.…”
Section: Gw0742 Mitigates the Ich-triggered Apoptotic Response In Thementioning
confidence: 85%
See 2 more Smart Citations
“…Previous studies have shown that activation of apoptosis plays an important role in the pathology of brain injury triggered by ICH [39,40]. The results of TUNEL staining (Fig.…”
Section: Gw0742 Mitigates the Ich-triggered Apoptotic Response In Thementioning
confidence: 85%
“…Neuronal death is a crucial pathological characteristic of ICH. Loss of neurons is strongly linked to the poor outcome of patients with ICH [40]. Many factors that activate post-ICH pathophysiological pathways cause cell death in perihematomal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyroptosis, as a pro‐inflammatory form of lytic cell death, is associated with pathogenesis in many chronic inflammatory diseases. Pyroptosis can be triggered by various pathological stimuli, such as microbial infection, heart attack, obesity, brain injury, and cancer (Bergsbaken, Fink, & Cookson, ; Bobinger, Burkardt, Huttner, & Manaenko, ; Liu et al, ). One hallmark characteristic of pyroptosis is membrane rupture, distinct from apoptosis, resulting in the release of intracellular pathogens, and pro‐inflammatory mediators (e.g., IL‐1β and IL‐18), which is induced by canonical inflammasomes activation, and can promote brain tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…The most common inflammasome sensors are absent in melanoma 2 (AIM2), and pyrin and nucleotide-binding oligomerization domain-like receptors (NLRs). The most prevalently studied inflammasome is NLR pyrin domain containing 3 (NLRP3) and it is thought to mediate various neurodegenerative and neurological disorders [22,27]. Pyroptosis involves the release of proinflammatory cytokines, especially IL-1β/IL-18; this, when combined with caspase-1 and inflammasome activity, causes the cells to swell and burst, thus leading to cell death.…”
Section: Pyroptosismentioning
confidence: 99%